Physical synthesis of Fe-Cu alloys via mechanical alloying - 'Alinurbi Binte Ahmad (Nanyang Technological University, 2023)
Soft magnetic materials are widely used as magnetic cores in transformers, motors, and generators as they can be easily magnetized and demagnetized. By using high-speed energy ball milling and spark plasma sintering to synthesise and consolidate Fe-Cu alloys, this project aims to understand the properties of various compositions of Fe-Cu. Characterisation techniques such as Scanning Electron Microscopy, X-ray Diffraction, Energy Dispersive X-ray Spectrometry, Vickers Hardness Test were employed to study the morphology, crystallography, magnetic and mechanical properties of the alloys. It was found that lower Cu content alloys, specifically lesser than 4% Cu, displayed the ferromagnetic nature and are promising for soft magnetic applications. However, this should not rule out the promising applications of the other compositions of Fe-Cu. Further study of the electrical and thermal properties of Fe-Cu alloys should be done to understand this metastable, immiscible system more holistically.